Do restrictive omnibus immigration laws reduce enrollment in public health insurance by Latino citizen children? A comparative interrupted time series study. (October 2017) - Allen, Chenoa D.; McNeely, Clea A.
Abstract: In the United States, there is concern that recent state laws restricting undocumented immigrants' rights could threaten access to Medicaid and the Children's Health Insurance Program (CHIP) for citizen children of immigrant parents. Of particular concern are omnibus immigration laws, state laws that include multiple provisions increasing immigration enforcement and restricting rights for undocumented immigrants. These laws could limit Medicaid/CHIP access for citizen children in immigrant families by creating misinformation about their eligibility and fostering fear and mistrust of government among immigrant parents. This study uses nationally-representative data from the National Health Interview Survey (2005–2014; n = 70, 187) and comparative interrupted time series methods to assess whether passage of state omnibus immigration laws reduced access to Medicaid/CHIP for US citizen Latino children. We found that law passage did not reduce enrollment for children with noncitizen parents and actually resulted in temporary increases in coverage among Latino children with at least one citizen parent. These findings are surprising in light of prior research. We offer potential explanations for this finding and conclude with a call for future research to be expanded in three ways: 1) examine whether policy effects vary for children of undocumented parents, compared to children whose noncitizen parents are legally present; 2) examine the joint effects of immigration-related policies at different levels, from the city or county to the state to the federal; and 3) draw on the large social movements and political mobilization literature that describes when and how Latinos and immigrants push back against restrictive immigration laws. Highlights: Adds to the growing evidence on the effects of immigration laws on Latino children. Examines the effects of restrictive state immigration laws on Medicaid/CHIP access. Uses multidisciplinary theories of symbolic policies and health care disparities. Suggests that community organizations may buffer the effects of restrictive laws. Argues for research on the intersection of laws at local, state, & federal levels.